Differentiating and Treating Painful Musculoskeletal Complications Associated with Diabetes - Vinall, Maria (MD Conference Express, 2014)
The effect of diabetes on muscles, tendons, bones, and ligaments often goes unrecognized. This article describes a number of musculoskeletal complications and how they affect patient care and outcome in people with diabetes. These musculoskeletal complications, which can become painful and cause patients to alter their daily routines, have a higher prevalence among those with long-standing type 1 and type 2 diabetes.